Thrombomodulin als Endothelzellmarker bei herzchirurgischen Patienten - Böhrer, Hubert; Böttiger, Bernd W.; Haußmann, R.; Nawroth, Peter Paul; Motsch, Johann; Martin, Eike (Anästhesiologie, Intensivmedizin, Notfallmedizin, Schmerztherapie, 1995)
Thieme E-Books & E-Journals